2023
DOI: 10.3389/fmolb.2023.1037966
|View full text |Cite
|
Sign up to set email alerts
|

Systematic analysis reveals novel insight into the molecular determinants of function, diversity and evolution of sweet taste receptors T1R2/T1R3 in primates

Abstract: Sweet taste is a primary sensation for the preference and adaption of primates to diet, which is crucial for their survival and fitness. It is clear now that the sweet perception is mediated by a G protein-coupled receptor (GPCR)-sweet taste receptor T1R2/T1R3, and many behavioral or physiological experiments have described the diverse sweet taste sensitivities in primates. However, the structure-function relationship of T1R2s/T1R3s in primates, especially the molecular basis for their species-dependent sweet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 53 publications
1
4
0
Order By: Relevance
“…Since the identification of human sweet taste receptor TAS1R2/TAS1R3 in 2001, substantial research has been steered to interactions between sweeteners and the receptor as well as the activation mechanism of sweet taste receptor. All findings verified the previous assumption that diverse sweeteners act on a common receptor. Based on its homology to other class C G-protein-coupled receptors (GPCRs) such as metabotropic glutamate receptors (mGluRs), the structure of heterodimeric human TAS1R2/TAS1R3 has been widely acknowledged with each subunit including an extracellular N-terminal Venus flytrap domain (VFD) and a heptahelical transmembrane domain (TMD), which are linked by a cysteine-rich domain (CRD) (Figure b) . Previous studies have shown that many sweeteners enter the pocket located at VFD of TAS1R2 (VFD2) or TAS1R3 (VFD3), while some bind to TMD of TAS1R3 (TMD3). , Sweet taste is initiated by a conformational closure of two lobes of VFD upon sweetener binding, followed by a signal transmission along CRD to TMD, and eventually induced by coupling with G protein and downstream signaling .…”
Section: Introductionsupporting
confidence: 79%
See 4 more Smart Citations
“…Since the identification of human sweet taste receptor TAS1R2/TAS1R3 in 2001, substantial research has been steered to interactions between sweeteners and the receptor as well as the activation mechanism of sweet taste receptor. All findings verified the previous assumption that diverse sweeteners act on a common receptor. Based on its homology to other class C G-protein-coupled receptors (GPCRs) such as metabotropic glutamate receptors (mGluRs), the structure of heterodimeric human TAS1R2/TAS1R3 has been widely acknowledged with each subunit including an extracellular N-terminal Venus flytrap domain (VFD) and a heptahelical transmembrane domain (TMD), which are linked by a cysteine-rich domain (CRD) (Figure b) . Previous studies have shown that many sweeteners enter the pocket located at VFD of TAS1R2 (VFD2) or TAS1R3 (VFD3), while some bind to TMD of TAS1R3 (TMD3). , Sweet taste is initiated by a conformational closure of two lobes of VFD upon sweetener binding, followed by a signal transmission along CRD to TMD, and eventually induced by coupling with G protein and downstream signaling .…”
Section: Introductionsupporting
confidence: 79%
“…(1) The identified “pincer residues” at the upper lobe (e.g., K65 and R383) and the bottom lobe (e.g., D278 and D307) of VFD2, which is an orthosteric binding region for majority of sweeteners, can be regarded as the interactive counterparts of AH and B glucophores, respectively. There are other potential residues (e.g., E302) with this behavior (Figure c), as shown in the complementary sweetener–receptor interactions described above. AH and B glucophores of sweeteners interact with these “pincer residues” to induce the conformational closure of two lobes of VFD2 to initiate receptor activation .…”
Section: Sars Of Various Sweeteners In Different Chemical Familiesmentioning
confidence: 76%
See 3 more Smart Citations